Trend Analysis of VR- and AR-Based Learning Media Development in Physics Education in the 2015–2025 Period - Handoko Bintoro; Mita Anggaryani; Mohd Zaidi Bin Amiruddin (Inovasi Pendidikan Fisika, 2025)
This study analyzes trends in the development of Virtual Reality (VR) and Augmented Reality (AR)-based learning media in physics education from 2015 to 2025. A systematic literature review (SLR) following the PRISMA framework was conducted, resulting in 103 selected articles. The analysis focuses on the distribution of physics topics, learning activities, instructional stages, and learning actors. The results show that VR/AR is predominantly used in mechanics and electromagnetism, while solid-state physics is least represented. Learning activities are mainly dominated by visualization/animation and experimental activities, highlighting the role of VR/AR in supporting interactive and experiential learning. These technologies are most frequently applied in the exploration stage, with limited use in the introduction stage. In addition, individual students are the primary users, indicating a strong emphasis on self-directed learning. Overall, VR and AR demonstrate strong potential to enhance conceptual understanding and engagement in physics learning, although their implementation remains uneven across topics and instructional contexts